Amoxicillin Extraction from Aqueous Solution by Emulsion Liquid Membranes Using Response Surface Methodology. Issue 1 (21st November 2018) - Seifollahi, Zahra; Rahbar-Kelishami, Ahmad
Abstract: The extraction of amoxicillin (AMX) from aqueous solutions by emulsion liquid membranes (ELMs) was investigated for the first time. The liquid membrane phase of the ELM consisted of Aliquat 336 as carrier, Span 80 as surfactant, n ‐hexane as diluent, and sodium chloride solution as internal phase. Response surface methodology (RSM) based on central composite design (CCD) was applied to evaluate and optimize the effects of several parameters such as carrier concentration, feed concentration, internal phase concentration, and treat ratio (volume ratio of the external phase to the emulsion phase). A polynomial model was fitted to predict the extraction yield of AMX. Under optimized conditions, the highest extraction yield of AMX was 99.8 %. Abstract : The antibiotic amoxicillin is hardly decomposed and difficult to remove from aquatic solutions. An innovative method of amoxicillin extraction using emulsion liquid membranes is proposed. The effects of process parameters on extraction using response surface methodology were evaluated. Under optimized conditions, an extraction yield of 99.8 % was achieved using the emulsion liquid membrane process.